Differential pattern of hand-tapping compromise in vascular versus idiopathic parkinsonism: a study based on computerized movement analysis - Bäzner, Hansjörg; Schanz, Jurik; Blahak, Christian; Grips, Eva; Wöhrle, Johannes C.; Hennerici, Michael G. (Movement disorders, 2005)
We tested the characteristics and the differential pattern of upper extremity motor compromise, comparing hand tapping in patients with subcortical vascular encephalopathy (SVE; n = 18), idiopathic Parkinson's disease (PD; n = 18), and in healthy controls (n = 18). Both patient groups showed significant compromise in hand tapping compared with that in controls, with higher coefficients of variability (CV) regarding tapping amplitude and angular velocity, determined using a computerized movement analysis system. A differential tapping pattern in both patient groups could be demonstrated in that patients with PD showed lower tapping amplitudes than patients with SVE. Both patient groups displayed abnormalities in tapping rhythmicity compared with that in the control group.
Gesehen am 12.05.2022